A highly specific and sensitive turn-on fluorescence probe for hypochlorite detection based on anthracene fluorophore and its bioimaging applications. (February 2019) - Wang, Zhonglong; Zhang, Yan; Song, Jie; Li, Mingxin; Yang, Yiqin; Gu, Wen; Xu, Xu; Xu, Haijun; Wang, Shifa
Abstract: Developing highly sensitive and specific methods for tracking hypochlorite (ClO − ) is highly desirable for unraveling its pathophysiological function in biological systems. Herein, a simple anthracene derivative (probe1 ) has been developed as a turn-on fluorescent probe for detecting ClO − in living cells. Probe1 exhibited excellent specificity for ClO − over other various biologically relevant species. Meanwhile, probe1 also showed a highly sensitive (145-fold fluorescence enhancement) response toward ClO − with a low detection limit of 3.17 nM. Probe1 could efficiently sense ClO − with a rapid response time and wide pH range in aqueous solution. The sensing mechanism was confirmed by NMR spectroscopic analysis and ESI-MS analysis. Density functional theory (DFT) calculations were employed for further estimating the optical behaviour of probe1 before and after the oxidation reaction with ClO − . Moreover, probe1 was quite suitable for the quantitative detection of ClO − in environmental water samples. Additionally, probe1 was successfully utilized to label exogenous ClO − in HeLa cells and endogenous ClO − in RAW 264.7 macrophage cells. Therefore, probe1 could be used as a promising method for monitoring ClO − in biological applications. Graphical abstract: Highlights: A novel fluorescent probe based on anthracene scaffold was designed and synthesized. The probe could be used for highly specific and sensitive detection of ClO − with fast response time. The probe could quantitatively detect ClO − in real environmental water samples. The probe was successfully applied to monitor the fluctuation of exogenous and endogenous ClO - in living cells.